Are Senior Entrepreneurs Happier than Who? The Role of Income and Health - Michael Fritsch; Alina Sorgner; Michael Wyrwich (Institute of Labor Economics (IZA), 2023)
We propose an extension of the standard occupational choice model to analyze the life satisfaction of senior entrepreneurs as compared to paid employees and particularly retirees in Germany. The analysis identifies income and health status as main factors that shape the relationship between occupational status and life satisfaction. Senior entrepreneurs enjoy higher levels of life satisfaction than retirees and senior paid employees. This higher life satisfaction is mainly due to their higher income. Physical and mental health play a crucial role in determining both an individual's occupational status and their overall life satisfaction. We find that senior self-employed report to be healthier compared to other groups of elderly individuals. However, when controlling for health, retirees exhibit an even higher level of life satisfaction compared to their self-employed counterparts. Heterogeneity analysis of various types of senior entrepreneurs and senior paid employees confirms this general pattern. In addition, we find some evidence indicating that senior entrepreneurs may compromise their leisure time, a main asset of retired individuals. Implications for research, policy, and practitioners are discussed.
Keywords: L26; I31; J10; D91; 330; senior entrepreneurship; health conditions; well-being; life satisfaction; age